End-tidal CO2 detection during cadaveric ventilation. Issue 9 (4th June 2015) - Coats, T J; Morgan, B; Robinson, C; Biggs, M; Adnan, A; Rutty, G
Abstract : 'Life like' end-tidal CO2 production has been reported in frozen cadaver during intubation training. We report the same phenomenon in a non-frozen cadaveric model used to undertake CT postmortem, with the additional findings of an increase in CO2 with chest compressions and an increase in CO2 after a pause in ventilation.